Heterogeneity versus homogeneity of multiple sclerosis - Sato, Fumitaka (2011)
The 10th International Congress of Neuroimmunology, including the 10th European School of Neuroimmunology Course, was held by the International Society of Neuroimmunology in Sitges (Barcelona, Spain) on 26–30 October 2010. The conference covered a wide spectrum of issues and challenges in both basic science and clinical aspects of neuroimmunology. Data and ideas were shared through a variety of programs, including review talks and poster sessions. One of the topics of the congress was whether multiple sclerosis is a homogenous or heterogenous disease, clinically and pathologically, throughout its course.